THE POLITICAL ECONOMY OF DEVELOPMENT IN INDIA: CHALLENGES, STRATEGIES, AND OUTCOMES - Nirmal, Ekanath Sitara (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the political economy of India’s development, analyzing the interplay between state policies, political institutions, and economic transformation. It examines the historical trajectory from colonialism to independence, the post-independence development strategies, economic reforms, and contemporary challenges. The paper argues that India’s development path is shaped by political decisions and societal pressures, with the state’s role in orchestrating development central to understanding the country’s economic success and failures.